SAK-EMKM Implementation of Medium Enterprise Financial Statement in Salatiga (Case Study of Medium Enterprise XZY in Salatiga) - Regina Aurellia Putri; Paskah Ika Nugroho (International Journal of Social Science and Business, 2020)
In order to evaluate Business Performance and make Small and Medium Enterprise easier to receive Business Credit Community, Ikatan Akuntan Indonesia (IAI) provides SAK EMKM (Financial Accounting Standards of Micro, Small and Medium Enterprises). SAK EMKM consists of Statement of Financial Position, Income Statement, and Notes to Financial Statement. Object of this research is Charcoal Briquette Producers that is categorized as Medium Enterprise located in in Salatiga. Purpose of this research is to educate and assist EMKM XYZ in arranging financial statement, since owner of this business does not understand what is SAK EMKM and how to apply it.